The Spheroplast Lysis Assay for Yeast in Microtiter Plate Format - Ovalle, Rafael (American Society for Microbiology (ASM), 1999)
A yeast lysis assay in the microtiter plate format improved precision and throughput and led to an improved algorithm for estimating lag time. The assay reproducibly revealed differences of 10% or greater in the maximal lysis rate and 50% or greater in the lag time. Clonal differences were determined to be the major source of variation. Microtiter-based assays should be useful for screening for drug susceptibility and for analyzing mutant phenotypes.